STUDI KOMPARASI SENI DAMBUS GAYA ZAROTI DAN KUSYADI DI BANGKA BELITUNG - Dodi Pranata, - (2023)
ABSTRACT This thesis is entitled Comparative Study of Zaroti and Kusyadi Style Dambus Art in Bangka Belitung. The problem of this research is '' How is the process of making dambus organologically and acoustically, Zaroti and Kusyadi's dambus playing techniques and Zaroti and Kusyadi's dambus playing style in performing songs?''. The purpose of this research is to describe and analyze the problems above. The method used is a descriptive analysis method with a qualitative approach. The research instrument is the researcher himself in the data collection process which is equipped with a video camera, photos, audio recordings, and field notes. The first resource person is a dambus craftsman and artist, namely Zaroti, while the second resource person in this study is Kusyadi with the same status. The results of the study show that the Zaroti and Kusyadi style dambus-making processes have similarities and differences. For the similarities, the two craftsmen chose the shape of the dambus head using deer antler motifs, while the differences included the selection of materials, tooling, manufacturing stages, sizes, shapes, strings and tuning systems in organology. The findings of the next question explain the game techniques of the two craftsmen which include bounce, slide, slur, tremolo, fingering, touching techniques and discuss styles in the position of finger placement, sitting and standing positions when the dambus is played. Furthermore, based on the last question, the presentation discusses how to perform the dambus song based on the form of arrangement or composition by Zaroti and Kusyadi which includes introduction, musical form, motifs, sentences, tangtut, sequences, symmetry, development, and cadence.